Party Institutionalization at the Local Level: The Case of Golkar in Merangin Regency’s 2024 Legislative Election - Rismawanti, Rima; Subekti, Dimas; Jeane Putri, Revi (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2026)
This study was motivated by the decline in votes and seats for the Golkar Party in Merangin Regency in the 2024 legislative elections. Whereas this party has consistently been the top performer in terms of vote share and seats in previous elections. Therefore, this study aims to explain the dynamics of the Golkar Party's consolidation in Merangin Regency in preparation for the 2024 legislative elections, using a party institutionalization perspective. The research method employed in this study is qualitative, with a case study approach. Data collection techniques include in-depth interviews and documentation. The results of this study show that the institutional consolidation of the Golkar Party in Merangin Regency for the 2024 legislative elections weak, contributing to the party’s decline in vote share and parliamentary seats. Weaknesses were identified across key dimensions of party institutionalization, including societal roots, organizational autonomy, organizational capacity, and internal coherence. The study contributes theoretically by reinforcing the argument that weak party institutionalization undermines electoral competitiveness. Furthermore, this study's findings provide insights into the dynamics of political party institutionalization at the local level, which is often overlooked in the national political literature